A LITERATURE REVIEW: DOES SUBJECTIVE CAREER SUCCESS AFFECT THE INTERNATIONAL HUMAN RESOURCES MANAGEMENT? - Setyanto Putro; Moh. Khoerul Anwar (UIN Sunan Kalijaga, 2022)
This paper aims to determine whether subjective career success can affect international human resource management. The method used is a literature study using articles and books. Based on these reading sources, global changes and technological advances are an important part of shaping one's personality and views, giving rise to a phenomenon in human civilization that continues to move in the global society and impacts international human resource management. The result of this article is an insight into international and global career perspectives, positioning of subjective career success and International HR management, cultural and environmental differences on subjective career success and International HRM, and the effect of subjective career success on International HR management.